Technical Assessment of the Oaxaca Water and Sanitation Sector Modernization Program - World Bank (Washington, DC, 2014)
In 2012 the Government of Oaxaca (GoO) prepared a Strategic Plan (Plan Estrategico Sectorial) for the Water Supply and Sanitation sector as part of its State Development Plan (Plan Estatal de Desarrollo) covering the period 2011-2016 corresponding to the six years of its administration. The objectives of the Strategic Plan for the WSS sector can be grouped under four pillars, expanding access to WSS services urban areas, improving water service quality and financial sustainability of water utilities, increasing wastewater treatment coverage, and expanding access to WSS services rural areas.